2019
DOI: 10.1371/journal.pone.0221269
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical stress and strain of maritime pilots in Germany. A cross-sectional study

Abstract: Introduction Maritime pilots work in an irregular deployment system (rotation system) with unpredictable work assignments under high levels of physical and mental stress. Fatigue or chronic diseases, e.g. coronary heart disease, peptic ulcers or gastritis can occur as a consequence. This can lead to long-term limitations of pilots’ work ability. The aim of this study is to analyse current stress and strain in maritime pilots. Methods Initially, all German pilots were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Maritime pilots on a four-month rotation system rated their subjective strain as ten times higher than those on one-week rotation systems, and reported more tiredness and more daytime sleepiness between pre- and post-rotation [ 70 ]. Incomplete recovery in between work shifts was positively associated with chronic fatigue [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maritime pilots on a four-month rotation system rated their subjective strain as ten times higher than those on one-week rotation systems, and reported more tiredness and more daytime sleepiness between pre- and post-rotation [ 70 ]. Incomplete recovery in between work shifts was positively associated with chronic fatigue [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Job Demand–Control model is also used to assess the relationship between psychological job demand and general fatigue, as well as reduced activity. 28 Therefore, occupational stress should not be ignored, due to its association with poor health and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 13 , 17 , 18 Negative consequences of stress have been observed also among certain other categories of pilots. Bauer et al, 27 studied the effect of occupational stress on helicopter emergency service pilots from four European countries while Barbarewicz et al, 28 investigated psychophysical stress among maritime pilots in Germany. In both studies, the side effects of occupational stress included general health and psychological problems including clenching of teeth and possible bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an unhealthy lifestyle is discussed as major risk factor among pilots. A former study revealed that this occupational group compared to the general population is more likely to exhibit overweight, smoking, high lipid serum levels, lack of physical activity and unhealthy eating habits [13].…”
Section: The Actual Piloting Takes Place On the Bridge In Pres-mentioning
confidence: 95%
“…Development of ship sizes of container vessels between the late 1990s and 2020. The biggest representatives after: Research-Information-System for Mobility and Traffic[13] …”
mentioning
confidence: 99%